Selection of DNA Aptamers for Ovarian Cancer Biomarker CA125 Using One-Pot SELEX and High-Throughput Sequencing - Delia J. Scoville; Tae Kyu Brian Uhm; Jamie A. Shallcross; Rebecca J. Whelan (Journal of Nucleic Acids)
CA125 is a mucin glycoprotein whose concentration in serum correlates with a woman’s risk of developing ovarian cancer and also indicates response to therapy in diagnosed patients. Accurate detection of this large, complex protein in patient samples is of great clinical relevance. We suggest that powerful new diagnostic tools may be enabled by the development of nucleic acid aptamers with affinity for CA125. Here, we report on our use of One-Pot SELEX to isolate single-stranded DNA aptamers with affinity for CA125, followed by high-throughput sequencing of the selected oligonucleotides. This data-rich approach, combined with bioinformatics tools, enabled the entire selection process to be characterized. Using fluorescence anisotropy and affinity probe capillary electrophoresis, the binding affinities of four aptamer candidates were evaluated. Two aptamers, CA125_1 and CA125_12, both without primers, were found to bind to clinically relevant concentrations of the protein target. Binding was differently influenced by the presence of Mg2+ ions, being required for binding of CA125_1 and abrogating binding of CA125_12. In conclusion, One-Pot SELEX was found to be a promising selection method that yielded DNA aptamers to a clinically important protein target.